Static Measurements on Adsorption of Gelatin onto Zinc-Powder Surfaces - Bajpai, A.K. (Asian Journal of Chemistry, 2010)
With an object to investigate the interactions between biopolymers and the metal surfaces, an adsorption experiment was carried out at room temperature and at constant pH = 4.0, which involved a study of the adsorption of weak polyelectrolyte biopolymer such as gelatin onto the surface of zinc powder. The adsorption isotherms were followed by estimating colorimetrically the residual concentration of gelatin in bulk of the solution after the adsorption experiment. The adsorption isotherms were found to be of medium affinity type and plateau adsorption was reached at relatively higher concentration of gelatin. The plateau adsorption was quite sensitive to the pH variation of the solution and was maximum near the isoelectric point of gelatin (4.8). The adsorption was also found to increase when the low molecular weight electrolyte like KCl was added in the concentration range of 0.01 to 0.08 mol/L. Furthermore, at higher concentration of the salt (> 0.08) the plateau adsorption decreased to a smaller degree.